The Role and Function of Non-Coding RNAs in Cholangiocarcinoma Invasiveness - Yu Meng; Fang Wei; Ye Zhang; Wenting He; Haijiao Yan; Jun Wu (Biomedicines, 2025)
Cholangiocarcinoma (CCA) is an aggressive tumor that originates from the epithelial cells of the bile duct and has the ability to metastasize to the liver or lymph nodes at an early stage. CCA metastasis represents a complex, multi-stage cascade process. Among these stages, the acquisition of invasiveness by CCA cells is a critical prerequisite for metastatic progression. Elucidating the molecular mechanisms driving CCA cell invasiveness is critical for advancing our knowledge in this field. Emerging evidence highlights the critical role of non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs). These molecules orchestrate key processes such as the epithelial–mesenchymal transition (EMT), as well as the migration and invasion of CCA cells. Collectively, these processes ultimately drive tumor progression. This review comprehensively synthesizes the expression, biogenesis, interactions, signaling pathways, and functional mechanisms of ncRNAs in the invasiveness of CCA. Furthermore, the review discusses potential clinical applications of ncRNAs, including their roles as diagnostic tools, therapeutic targets, and prognostic markers. These investigations offer novel insights and evidence for identifying early metastasis in CCA, developing specific therapeutic strategies, and enhancing drug resistance.